ANALISIS KINERJA PEGAWAI BIDANG P2LKD PADA DINAS PEMBERDAYAAN MASYARAKAT DAN DESA KABUPATEN SUMEDANG - Kusdinar, Rika; Febryani, Annisa Dwi; Saputra, Wizdan; Hapit, Rosnia Nur; Septiani, Fanny; Pratama, Ikhsan Fauzi (JRPA - Journal of Regional Public Administration, 2024)
This study aims to analyze the performance of employees in the field of P2LKD (Community and Village Empowerment) of the Sumedang Regency Community and Village Empowerment Office. Employee performance is a crucial factor in the successful implementation of the P2LKD program which aims to improve community welfare at the village level. This research methodology involves collecting employee performance data through observation, interviews, and analysis of related documents. Performance analysis is carried out using an evaluation framework that includes aspects such as productivity, competence, dedication, and interpersonal skills. The results of this study are expected to provide a comprehensive picture of employee performance in the field of P2LKD, identify potential improvements, and provide recommendations to improve the effectiveness and efficiency of the implementation of Community and Village Empowerment programs in Sumedang Regency. With a deep understanding of employee performance, it is hoped that the results of this research can be the basis for improving policies and strategies for human resource management at the Community and Village Empowerment Office, so that they can make a maximum contribution in achieving development goals at the village and community levels.